TERRITORIAL COMMUNITIES’ COOPERATION (INTERMUNICIPAL COOPERATION – IMC) AS AN INNOVATIVE TOOL FOR ENSURING LOCAL ECONOMIC DEVELOPMENT AND MUNICIPAL CONSOLIDATION - Tolkovanov, Vyacheslav (Науковий вісник Полісся, 2017)
Urgency of the research. The importance of studying the different aspects of the development of the territorial communities’ cooperation (intermunicipal cooperation - IMC) is explained by the fact that IMC is defined as a priority of local self-government reform in Ukraine. It is also used by the different European countries as an innovative tool for ensuring local economic growth and sustainable development. Target setting. It is reasonable to study the different aspects of IMC development (institutional, legal, financial etc.) and to highlight the best IMC practices in order to give reasons for the possibilities of its implementation in Ukraine and ensuring municipal consolidation. Actual scientific researches and issues analysis. The scientific works of such scholars as V. Kniazev, N. Kostina, V. Kuybida, N. Mikula, N. Nyjnyk, M. Pukhtynskiy, T. Pakhomova, O. Povajniy, S. Romanuk, A. Tkachuk and others deal with the different aspects of IMC development. Uninvestigated parts of general matters defining. The scientists have not yet sufficiently developed the argumentation of more active using of IMC different forms in the framework of the implementation of local self-government reform in Ukraine. The research objective. The article aims to highlight the current status and the new approaches for IMC development in the framework of the implementation of the decentralization reform in Ukraine. The statement of basic materials. The article proves the expediency of using IMC as an innovative tool for ensuring sustainable local development. The special attention is paid to the analysis of the new legislation on territorial communities’ cooperation as well as the activity of the main institutions on all levels. The author provided a deep analysis of the best international and national practices in the field of IMC as well as prepared the relevant recommendations for >its further development. Conclusions. IMC represents an integrative part of the local self-government reform in Ukraine. Taking into account the successful implementation of the pilot projects (in particular, in Poltava region), IMC could be used for further municipal consolidation and local economic development.